2019
DOI: 10.1038/s41467-019-12903-1
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced hydrogen release from hydrogen boride sheets

Abstract: Hydrogen boride nanosheets (HB sheets) are facilely synthesized via ion-exchange treatment on magnesium diboride (MgB2) in an acetonitrile solution. Optical absorption and fluorescence spectra of HB sheets indicate that their bandgap energy is 2.8 eV. According to first-principles calculations, optical absorption seen at 2.8 eV is assigned to the electron transition between the σ-bonding states of B and H orbitals. In addition, density functional theory (DFT) calculations suggest the other allowed transition f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 31 publications
12
102
0
Order By: Relevance
“…HB sheets were prepared using a previously reported ionexchange method. [17][18][19][20][21][22] More specifically, MgB 2 powder (1.0 g, 99%, Rare Metallic Co., Ltd, Tokyo, Japan) in acetonitrile (300 mL, 99.5%, Wako Pure Chemical Industries Ltd, Osaka, Japan) was added to a mixture of an ion-exchange resin (60 mL, Amberlite IR120B hydrogen, Organo Corp., Tokyo, Japan) and acetonitrile (200 mL) in a Schlenk flask under a nitrogen atmosphere. Water was carefully removed due to the facile hydrolysis of MgB 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HB sheets were prepared using a previously reported ionexchange method. [17][18][19][20][21][22] More specifically, MgB 2 powder (1.0 g, 99%, Rare Metallic Co., Ltd, Tokyo, Japan) in acetonitrile (300 mL, 99.5%, Wako Pure Chemical Industries Ltd, Osaka, Japan) was added to a mixture of an ion-exchange resin (60 mL, Amberlite IR120B hydrogen, Organo Corp., Tokyo, Japan) and acetonitrile (200 mL) in a Schlenk flask under a nitrogen atmosphere. Water was carefully removed due to the facile hydrolysis of MgB 2 .…”
Section: Methodsmentioning
confidence: 99%
“…17 HB sheets are terminated by protons on the negatively charged hexagonal boron sheets and they are known to exhibit versatile properties, such as a large H 2 content (8.5 wt%), semimetal electronic properties, 18,19 metal ion reducibility, 20 and a light-responsive hydrogen release function. 21 Our recent study revealed that HB sheets in their hydrogen-deficient state (H : B ratio of approximately 1 : 2.5 AE 0.5) catalyze the conversion of ethanol to ethylene and water above 493 K with high selectivity independent of the contact time, and an apparent activation energy of 102.8 AE 5.5 kJ mol À1 . 22 The activation energy of this process is comparable to those reported for the catalytic dehydration of ethanol over Al 2 O 3 (53-155 kJ mol À1 ), 23,24 the Lewis acidic catalyst Zr-KIT-6 (79 kJ mol À1 ), 25 silica-alumina (125.5 kJ mol À1 ), 26 and the microporous Fe-ZSM-5 (137.7-271.1 kJ mol À1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, connections between the polyhedral boranes and the metal borides can be drawn [13] . Notably, recent works have shown that extraction of a single hexagonal layer of boron atoms from superconducting MgB 2 is possible in the form of 2‐D borane layers (BH) 1 , [14–18] known as borophane, hydrogen boride or hydrogenated borophene. This 2D (BH) 1 hexagonal structure is very similar to graphene [19] with two exceptions, apart from the atom nature: (i) there are two different B–B distances for each hexagon, short d (BB) and long d (BB) b and (ii) there are two bridge hydrogen atoms (H b ), one above and one below the xy plane in the mid‐point of every alternating long (BB) b bond, as shown in Figure 1b.…”
Section: Introductionmentioning
confidence: 99%
“…Boron and its compounds are used in the chemical, medicinal, and nuclear industries [1][2][3]. Due to their extensive application in areas such as electronic products, advanced materials, and new energy vehicles, boron resources are designated as indispensable mineral resources for emerging strategic industries [4][5][6]. Chinese boron reserves rank fifth globally at 24 million tons (B 2 O 3 ) [7].…”
Section: Introductionmentioning
confidence: 99%